ANALISIS KINERJA SIMPANG BERSINYAL AKIBAT MARKA JALAN YELLOW BOX JUNCTION PADA SIMPANG EMPAT TANAH AJI, KOTA MATARAM - MAHENDRA, MADE; HASYIM, HASYIM (Ganec Swara, 2025)
One of the intersections in Mataram City that uses Yellow Box Junction markings is at Simpang Empat Tanah Aji, which is a point prone to traffic jams in Mataram City due to its role as an access road to the center of community activities. Therefore, this study was conducted to determine the intersection performance at Tanah Aji Intersection Four due to Yellow Box Junction markings based on PKJI 2023, determine the percentage of violations of Yellow Box Junction markings, determine the percentage level of public understanding of Yellow Box Junction markings and determine whether the Yellow Box Junction markings at Tanah Aji Intersection Four are in accordance with Ministerial Regulation No. 34 of 2014. From the results of the intersection performance analysis, the DJ = 2.81 value is obtained for existing traffic conditions and DJ = 2.79 for traffic conditions due to the Yellow Box Junction markings. Based on PKJI 2023, the value of DJ> 0.85 indicates poor performance due to the traffic flow at the intersection approaching its saturation flow so that it can be judged that the Yellow Box Junction markings at the Tanah Aji Four Intersection cannot improve intersection performance. From the observation of violations, the percentage of violators is 13.82% with the percentage of motorcycle violators 11.36%, passenger cars 2.39%, and heavy vehicles 0.07%. From the results of the online questionnaire, the level of public understanding of the placement of markings at the Tanah Aji Four Intersection is 84.25%, definition 50.5%, function 49.75%, how to use 45.75%, and legal aspects 16.75%. There were also 44% of people who stated that they had violated and 67% of people considered these markings effective in overcoming congestion. From the results of observations and measurements related to the suitability of the markings to Ministerial Regulation No. 34 of 2014, the results obtained are not suitable for a straight line width of 30 cm because it exceeds the applicable provisions and there is also the center of the markings covered by a new layer of pavement.